Electrochemical properties of a rechargeable aluminum–air battery with a metal–organic framework as air cathode material. Issue 11 (19th January 2017) - Mori, Ryohei
Abstract : The goal of this study was to develop a rechargeable aluminum–air battery with high capacity and long-term durability in charge–discharge electrochemical reactions. Abstract : The goal of this study was to develop a rechargeable aluminum–air battery with high capacity and long-term durability in charge–discharge electrochemical reactions. We used aluminum terephthalate as a metal–organic framework (MOF) material for the air cathode and 1-ethyl-3-methylimidazolium chloride as an ionic liquid electrolyte. When we used aluminum terephthalate as an air cathode material, the electrical power output and cell capacity were lower than that attained with the cell using activated carbon as air cathode material. However, the cell capacity, cyclic voltammetry behavior, and cell interfacial impedance was more stable over repeated electrochemical reactions when the MOF was used as an air cathode material. In addition, we did not observe Al(OH)3 and Al2 O3 on the anode electrodes, which are byproducts that inhibit aluminum–air battery function.